G-matrix Fourier transform NMR spectroscopy for complete protein resonance assignment - Atreya, Hanudatta S. (National Academy of Sciences, 2004)
A G-matrix Fourier transform (GFT) NMR spectroscopy-based strategy for resonance assignment of proteins is described. Each of the GFT NMR experiments presented here rapidly affords four-, five-, or six-dimensional spectral information in combination with precise measurements of chemical shifts. The resulting high information content enables one to obtain nearly complete assignments by using only four NMR experiments. For the backbone amide proton detected “out-and-back” experiments, data collection was further accelerated up to ≈2.5-fold by use of longitudinal (1)H relaxation optimization. The GFT NMR experiments were acquired for three proteins with molecular masses ranging from 8.6 to 17 kDa, demonstrating that the proposed strategy is of key interest for automated resonance assignment in structural genomics.